Pengembangan Sistem Informasi Pendataan Jemaat Gereja Masehi Advent Hari Ketujuh Konferens Jawa Kawasan Timur Berbasis Web - Yuliawan, Yeremia; Sunarto, M. J. Dewiyani; Soebijono, Tony (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2013)
Konferens Jawa Kawasan Timur(KJKT) has an organization that aims to help the part of the task, the vision and mission of the ministry in the church. With the number of church members were 68 (sixty eight), Konferens Jawa Kawasan Timur must also have accumulated a very large. Associated with today's technological advances, Adventist churches in the region of Konferens Jawa Kawasan Timur was to collect data on the church, so that the central secretariat in charge of the church having difficulty logging collect and process data in the congregation who are Seventh-day Adventist Church in eastern Java. Seeing the conditions that exist today, it is so lacking assist the Konferens Jawa Kawasan Timur do some of the work of data collection in Adventist Church in eastern Java. With Information Systems Development Church of Seventh-day Adventist Church Konferens Jawa Kawasan Timur, is expected to help the congregation who has been running the data collection in order to be processed properly. Well-organized data will help the treatment process. So, in the end reports can be generated and used by the conference as a basis for decision-making activities that have been defined as the annual work program of the annual conference eastern Java. Keywords: Seventh-day Adventist Church, Konferens Jawa Kawasan Timur, Church Information System